Development of Ecoprint Skills into Creative Entrepreneurship Products at Muhammadiyah Vocational School Gamping Sleman: Pengembangan Keahlian Ecoprint Menjadi Produk Kreatif Kewirausahaan di SMK Muhammadiyah Gamping Sleman - Amelia Tri Budi Astuti; Budiman, Ahmad Satria; Rina Afiani Rebia; Febrianti Nurul Hidayah; Ade Primananda; Adella Medika Khairun Nisa; Dean Akbarocta (Universitas Lancang Kuning, 2023)
Based on observations and interviews conducted at SMK Muhammadiyah Gamping Sleman, there areproblems that can be solved through the community service activities, that is waste of leaves which have potential to become textile products. This can also be an alternative for developing skills and a synergy with school subjects whichecoprinting has never been taught at SMK Muhammadiyah Gamping Sleman. The methods used include: 1) Ecoprint training using steaming and pounding techniques; 2) Creative products-making; and 3) Digital marketing training in the field of fashion. The results of these activities areboth students and teachers are able tomake ecoprint fabric, process it into creative products, and undertstand digital marketing. Furthermore, the results of a questionnaireconducted byparticipants showed that there are beneficial values, both for individuals and school subjects, as well as an increase in ecoprint knowledge. Thus, it can be concluded that this community service is on target and achieves its goals